Ingesting Jesus: Eating and drinking in the Gospel of John - Webster, Suzanne Jane (My University, 2001)
The Gospel of John often uses ingesting language. First, it refers to concrete elements of food and drink (such as bread, water, fish and wine) and the actions of eating and drinking. Second, it uses metaphors of food and drink; for example, Jesus is the "bread of life" and the "source of living water." Third, it uses meals as the setting for much of the narrative. The prevalence of ingesting language in various contexts and genres establishes it as a primary literary motif in the Gospel of John. While the individual passages involving food, drink and ingesting have not gone unnoticed in the history of Johannine scholarship, no major monograph has addressed the motif as a whole nor drawn specific conclusions about its function in the Gospel. Drawing on the literary theory of William Freedman, this study first extends the limits of the ingesting motif to include phrases drawn from the semantic domain of ingestion as well as narrative contexts that have been excluded, for the most part, from previous studies. By extending these limits, this study affirms more emphatically the relationship between eating and drinking and the death of Jesus. In particular, ingesting language provides a way to describe both the role of Jesus as the one who is incarnate as "flesh" but who must die in order that others might eat and live, and the role of the believer who is "to eat and drink Jesus." This study will thus argue that the ingesting motif serves as a vehicle for Johannine soteriology. This conclusion has implications for the extended debate concerning Eucharist traditions in the Johannine literature, for although the Eucharist is not specifically mentioned in the Gospel, the prevalence of the ingesting motif suggests that eating and drinking play a significant role in the Johannine understanding of salvation.
Keywords: Religion; Religion